Reaction of rat connective tissue to implanted dentin tubes filled with mineral trioxide aggregate or calcium hydroxide - Holland, Roberto [UNESP]; Souza, Valdir de [UNESP]; Nery, Mauro Juvenal [UNESP]; Otoboni Filho, José Arlindo [UNESP]; Bernabé, Pedro Felício Estrada [UNESP]; Dezan Junior, Eloi [UNESP] (Elsevier, 1999)
This study was conducted to observe the rat subcutaneous connective tissue reaction to the implanted dentin tubes filled with calcium hydroxide or mineral trioxide aggregate. The animals were sacrificed after 7 and 30 days, and the specimens were prepared for morphological study. Some undecalcified specimens were prepared for histological analysis with polarized light and Von Kossa technique for calcium. The results were similar for both studied materials. At the tube openings, there were Von Kossa-positive granules that were birefringent to polarized light. Next to these granulations, there was an irregular tissue like a bridge that was Von Kossa-positive. The dentin walls of the tubes exhibited in the tubules a structure highly birefringent to polarized light, usually like a layer and at different depths. It is possible that the mechanism of action of both materials has some similarity. Copyright © 1999 by The American Association of Endodontists.
Keywords: aluminum derivative; calcium derivative; calcium hydroxide; mineral trioxide aggregate; oxide; root canal filling material; silicate; animal; connective tissue; dentin; drug combination; drug effect; human; implant; rat; Aluminum Compounds; Animals; Calcium Compounds; Calcium Hydroxide; Connective Tissue; Dentin; Drug Combinations; Humans; Implants, Experimental; Oxides; Rats; Root Canal Filling Materials; Silicates